And Then It Was Fixed . . .: The Storytelling that Surrounds Cunning Folks - Munk, Kirstine (Bulletin for the study of religion, 2013)
The cunning folks have always existed in Denmark. They cure various ailments and are often surprisingly succesful despite the fact that they do not have any education relevant to their practice. The cunning people seldom advertice, and their reputation is based exclusively on the stories that other people tell about them. This article explores why the narratives abut the cunning people seem to be such good stories, when - in comparison - the stories that are generated in the mainline alternative health sector are less fabulous.